Sex differences in growth and performance of track and field athletes 11-15 years - Malina, R. M.; Slawinska, T.; Ignasiak, Z.; Rozek, K.; Kochan, K.; Domaradzki, J. Fugiel, J. (Journal of Human Kinetics, 2010)
Objective: To evaluate sex differences in functional performances of youth track and field athletes. Methods: Four tests of functional capacity were administered to 309 youth 11-15 years training for track and field at sport schools, 136 boys and 173 girls. Grip strength, standing long jump, 2 kg medicine ball throw and 20 m sprint were measured; height, weight and adiposity were also. Two age groups were compared, 11-13 and 14-15 years. ANCOVA was used to test sex differences by age group in the total sample (disciplines combined) and specific disciplines; age, height and weight were covariates. Results: For the total sample, males in both age groups performed better than females in the four tests but sex differences were greater among 14-15 year olds. Within disciplines, sex differences among sprinters and middle distance and distance runners were greater at 14-15 years. Results varied for general athletics; the magnitude of sex differences was similar for strength in both age groups, greater for the throw at 11-13 years and greater for the jump and sprint at 14-15 years. Conclusion: Although sex differences in performance were apparent among athletes 11-13 years, they were greater among athletes 14-15 years, reflecting to a large extent the male adolescent spurt in body size, muscle mass, strength and power. Sex differences were more established in sprinters and middle distance and distance runners, and more variable in participants in general athletics.